Characteristic Analysis of Bending Fatigue Stress of Asymmetric Gear with Small Teeth Number - Cai Youjie (Jixie chuandong)
On the development of miniaturization,lightweight and energy efficiency for mechanical transmission device,asymmetric gear with small teeth number attracts a lot of interests in both fundamental research and application,but the study of the bending fatigue stress characteristics is few. Based on the principle of gear machining,the gear tooth profile equations is built,the analytic calculation method including asymmetric tooth profile and tangential displacement of asymmetric gear with a small number of teeth gear bending stress is proposed and the calculation results are compared with the results of finite element method. The asymmetric and symmetrical gears with small teeth number are high efficiency machined by numerical control machining method. Their bending fatigue strength is tested by high-frequency fatigue testing machine,and the results for different stress level are analyzed and discussed by using the fatigue cumulative failure hypothesis. The complete and true C-R-S-N curves are obtained,which provides the basis for the estimation of the bending fatigue life of the asymmetric gear with small teeth number. The results show that,by the analytical method,the asymmetric gear bending strength is 13. 64% higher than that of symmetric gear,by finite element method is14. 78% higher than that of symmetric gear. Under the same load,the bending fatigue life of asymmetric gear with small teeth number is average increased 46. 86%. The same trend with the analytical method and the finite element method calculation results,a reference for such research method is provided.